NaCl 스트레스에 따른 출수기 시기의 엽록소 측정을 활용한 밀 핵심집단의 전장유전체연관 분석 - 민경도(Kyoung Do Min), 현도윤(Do Yoon Hyun), 박상용(Sang Yong Park), 김재윤(Jae Yoon Kim) (Korean journal of breeding, 2025)
Salt stress is a major abiotic factor that limits wheat production worldwide. However, this threat is increasing significantly because soil salinity affects approximately 20% of the irrigated agricultural land globally, leading to significant yield losses by impairing plant growth and photosynthetic efficiency. This study aimed to identify single-nucleotide polymorphisms (SNPs) associated with salt tolerance in wheat core collections during the heading stage under saline stress conditions. Chlorophyll content, a physiological indicator of salt tolerance at heading, and soil electrical conductivity (EC) were measured in 609 accessions and a Salt Tolerance Index (STI) was subsequently constructed. Genome-wide association studies (GWAS) were performed using a 35 K SNP chip to identify significant marker-trait associations. Three models (MLM, FarmCPU, and BLINK) were employed for the GWAS, with FarmCPU and BLINK demonstrating superior power over the MLM in controlling false positives. GWAS results revealed four significant SNPs (AX-94929101, AX- 94615611, AX-94510535, and AX-94411611) located on chromosomes 3D, 5D, and 7D. AX-94510535 exhibited significant phenotypic differences based on SNP genotype, suggesting its potential as a marker for STI. Furthermore, the identified candidate genes, TraesCS3D02G218100, TraesCS5D02G059500, and TraesCS5D02G175000, were implicated in biological processes such as DNA replication, cell death, and photosynthesis. KCI Citation Count: 0